The Importance of Islamic Values in the Views of Lecturers: A Survey Analysis - Srimulat, Fitri Endang; Eriyanti, Ribut Wahyu; Rofiq, Ainur; Huda, Atok Miftahul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: religious values play an important role in shaping students' character and morals, and understanding lecturers' views regarding this can provide in-depth insights for improving higher education. Aim: analyze lecturers' perceptions of Islamic values, focus on understanding their level of awareness, integration of religious values in the curriculum, the role of lecturers in forming character, institutional support, and the influence of understanding Islamic values on student morale. Method: This research uses a survey method involving 60 lecturers as respondents. The survey involved structured questions covering the level of importance of Islamic values, integration in the curriculum, the role of lecturers, institutional support, and views on the influence of understanding Islamic values on student morale. Results and Discussion: Survey results show that the majority of lecturers are aware of the importance of Islamic values (91.6%) and the majority (80%) feel that these values are sufficiently integrated in the curriculum. Support for the role of lecturers in forming Islamic character is high (88.4%), and most lecturers (78.3%) feel they receive adequate institutional support. Overall, the results show a positive view of lecturers towards Islamic values. The conclusion of this research highlights the importance of supporting lecturers in strengthening their role as character-forming agents and emphasizes the need for the integration of religious values in the higher education curriculum. The implications of these findings can help design more holistic educational policies and strategies, creating an educational environment that focuses on developing student character and morality.